Use of metamizole and other non-opioid analgesics in Switzerland between 2014 and 2019: an observational study using a large health insurance claims database (Swiss Medical Weekly, 2024)
OBJECTIVE: To investigate claims patterns for metamizole and other non-opioid analgesics in Switzerland. To characterise users of these non-opioid analgesics regarding sex, age, comedications and canton of residence.METHODS: We conducted a retrospective descriptive study using administrative claims data of outpatient prescribed non-opioid analgesics of the Swiss health insurance company Helsana between January 2014 and December 2019. First, we evaluated the number of claims and defined daily doses  per year of metamizole, ibuprofen, diclofenac and paracetamol in adults aged 18 years or over. Second, we characterised new users of these non-opioid analgesics in terms of sex, age, claimed comedications and canton of residence.RESULTS: From 2014 to 2019, among the investigated non-opioid analgesics, metamizole showed the highest increase in claims (+9545 claims, +50%) and defined daily doses (+86,869 defined daily doses, +84%) per 100,000 adults. Metamizole users had the highest median age (62 years [IQR: 44–77]) compared to ibuprofen (47 years [IQR: 33–62]), diclofenac (57 years [IQR: 43–71]) and paracetamol (58 years [IQR: 39–75]) users. Metamizole users also more frequently claimed proton pump inhibitors, anticoagulants, platelet aggregation inhibitors and antihypertensive drugs than users of other non-opioid analgesics. While metamizole was most frequently claimed in German-speaking regions of Switzerland, ibuprofen and paracetamol were most frequently claimed in the French-speaking regions and diclofenac in German- and Italian-speaking regions.CONCLUSION: In Switzerland, metamizole was increasingly claimed between 2014 and 2019. Metamizole was most frequently claimed by older adults and patients with comedications suggestive of underlying conditions, which can be worsened or caused by use of nonsteroidal anti-inflammatory drugs. The lack of studies regarding the effectiveness and safety of metamizole in this population warrants further investigation.